Bombyxin (Bombyx Insulin-Like Peptide) Increases the Respiration Rate Through Facilitation of Carbohydrate Catabolism in Bombyx mori - Kawabe, Yuko; Waterson, Hannah; Mizoguchi, Akira (Frontiers in Endocrinology, 2019)
Bombyxin-II, an insulin-like peptide of the slkmoth Bombyx mori, has been shown to reduce both the trehalose concentration in the hemolymph and glycogen content in some tissues of B. mori larvae. However, little is known about how these storage carbohydrates are utilized. To address this question, the effects of bombyxin-II injection into Bombyx larvae on the tissue lipid level, respiration rate, and glycolytic activity of tissues were investigated. Bombyxin-II did not affect lipid accumulation in the hemolymph and fat body, while it increased the rate of oxygen consumption and increased the content of fructose 2, 6-bisphosphate, a potent activator of glycolysis, in the gonads, imaginal discs, and midgut. These results suggest that bombyxin facilitates cellular energy production thereby supporting the tissue growth of insects.